Initial experience in direct graft perfusion assessment following orthotopic liver transplant - A. V. Moiseenko; A. A. Polikarpov; P. G. Tarazov; D. A. Granov (Вестник трансплантологии и искусственных органов)
Objective: classical methods of determining arterial blood supply of the graft following orthotopic liver transplantation (OLT) reflect the presence of blood flow in the trunk and large branches of the A. hepatica, without the characteristic of completeness of blood filling of peripheral sections, which is very important for objective evaluation of function. The aim of this study is to establish the diagnostic value of a direct perfusion study (IFlow) of the graft. Materials and methods. From 1998 to 2019, 245 OLTs were conducted. From 2015 to 2019, arterial changes were detected in 24 (23%) patients after 104 OLTs. A perfusion study was performed in 9 patients with suspected arterial graft failure. According to the IFlow study, liver hypoperfusion due to stenosis and/or splenic steal syndrome was detected in 8 cases and became an indication for therapeutic intervention. Results. Hepatic stenting and/or splenic artery embolization was performed to improve arterial blood supply to the liver. Endovascular procedures performed restored the perfusion index from 0.24 (0.01–0.89) to 0.61 (0.35–0.98). Conclusion. Absence of ultrasound and multispiral computed tomography signs of arterial complications does not rule out the need for perfusion angiography. Perfusion angiography allows to objectify the angiography data and perform corrective intervention in good time.